Cosmological Consequences of Gravitation: Structure Formation and Gravitational Waves - Book, Laura Grace (California Institute of Technology, 2012)
This thesis contains work on four topics which fit into two broad areas of research: the quest to understand structure formation and through it the properties of the dark matter, and the search for primordial gravitational radiation. The first project details the effect of an accretion shock on the colors of satellites in galaxy clusters. A new model of ram pressure stripping including an accretion shock with variable radius is developed and implemented in the Galform semi-analytic model of galaxy formation. A comparison of this model with previous models and with observations indicates that current data is unable to discriminate between models, though future observations will be able to place stronger constraints on the role of ram pressure stripping in and around clusters.

Next, an analysis of the angular momentum evolution of dark matter particles in high-resolution N-body simulations of dark matter halos is presented. We find that individual particle angular momentum is not conserved, and also that the angular momentum of radial shells varies over the age of the Universe by up to factors of a few. These results have serious implications for the validity of current analytical models that assume angular momentum conservation.

Two methods for detecting the primordial gravitational wave (GW) background are then presented. Such a background, if detected, could greatly impact our understanding of the early universe. The first proposed method uses the apparent angular velocities of astrophysical objects induced by GWs, which may be detectable with upcoming astrometric missions such as the GAIA satellite. This work improves upon previous order-of-magnitude estimates, and presents a full calculation of the expected signal from a stochastic background of GWs.

The second method uses bipolar spherical harmonics decomposition, a formalism to characterize departures from statistical isotropy and Gaussianity, to quantify the expected lensing of the cosmic microwave background (CMB) and 21 cm radiation by GWs. The lensing of the CMB by GWs is found to not be detectable, but that of future 21 cm surveys could give a very high quality measurement of the primordial GW background.
Keywords: Cosmic Microwave Background; Gravitational Waves; Angular Momentum; N-Body Simulations; Physics; Structure Formation; Astrometry